ANALIZA DYSKURSU W GLOTTODYDAKTYCE SPECJALISTYCZNEJ: KRYTERIA DOBORU MODELI TEORETYCZNYCH DLA POTRZEB DYDAKTYKI SZKOLNEJ - Gajewska, Elżbieta (Neofilolog, 2020)
The recent decision of the Polish Ministry of National Education to make specialized language a compulsory part of vocational training sets the context of this argument. Teachers of professional secondary schools will now face new methodological challenges, so it is important to give them appropriate tools to address these. This paper examines the best known models of genre analysis used in the study of LSP : Bhatia (1993); Askehave and Swales (2000), and the Analyse Différentielle des Discours: Mourlhon-Dallies (2008), reflecting on the possibilities of their practical use in the teaching of LSP.